Try574 leu mutation confers cross-resistance to ALS-inhibiting herbicides in wild radish Mutação Try574 conferindo resistência cruzada a herbicidas inibidores da ALS em nabiça - Fruet D.L.* (2024)
© 2024, Universidade Federal Rural do Semi-Arido. All rights reserved.Understanding how weeds resist herbicides, their resistance mechanisms, and alternative control methods are crucial for managing herbicide-resistant weeds. This study aims to unravel the resistance mechanism of a Raphanus raphanistrum biotype to acetolactate synthase (ALS) inhibitors. To this end, dose-response studies, DNA sequencing, and metabolic pathway verification were conducted. ALS-inhibiting herbicides showed low efficacy in controlling this biotype, confirming cross-resistance. Sequencing of the ALS enzyme revealed the presence of the previously reported Try-574-Leu mutation, known to confer cross-resistance to this mode of action. However, the metabolization verification assay demonstrated that this mechanism did not contribute to the observed resistance. Chemical control studies with alternative herbicides yielded promising results, indicating the potential for effective management of the resistant biotype. Our findings showed that the wild radish biotype used exhibits cross-resistance to ALS-inhibiting herbicides due to the presence of the Try-574-Leu mutation in the target enzyme. Notably, herbicides with alternative mechanisms of action prove highly effective in controlling this resistant biotype, offering valuable options for weed management strategies.